Axisymmetric modes, fast ions and X-point effects in tokamak plasmas. Issue 1 (1st December 2022) - Barberis, T.; Porcelli, F.; Fitzpatrick, R.; Yolbarsop, A.
Abstract: Recent progress on the understanding of axisymmetric pertubations in tokamak plasmas is presented, with particular attention on Vertical Displacement Oscillatory Modes (VDOM) that can be driven unstable by their resonance with fast ion orbits, and on the impact of divertor X-points on the stability of vertical displacements.